AWARENESS OF WOMEN TOWARDS AN EMERGING THREAT - Yousuf, Farhana; Haider, Gulfareen; Muhamma, Nasirudin; Haider, Ambreen (Journal of Ayub Medical College Abbottabad, 2009)
Background: The human immunodeficiency virus/Acquired immunodeficiency syndrome (HIV/AIDS) pandemic continues it deadly assault in different parts of the world. Over 20 million people have died since the first case of AIDS was identified in 1981. Despite increased spending on HIV/AIDS programmes and improved responses by many governments, current global efforts remain entirely inadequate for an epidemic that is continuing to spiral out of control. The objective of this study was to determine the level of awareness about HIV and AIDS among women attending the obstetrics and gynaecology clinic. Methods: This Descriptive study was conducted in the Obstetric & Gynaecology clinic at LUMHS, Hyderabad Pakistan from 5th July 2007 to 3rd Dec 2007. A total of 178 women attending obstetric and gynaecology clinic of age 20-55 years were selected randomly. Information was collected by pre-designed questionnaire to assess the level of awareness about HIV/AIDS. Results: About 83.7% women had heard about HIV/AIDS and only 44.3% correctly stated the difference in HIV/AIDS. Only 41.5% of respondents knew how would infected person present, and 55.6% respondents knew that it is transmitted through close sexual relationship, while less than 50% correctly answered about mode of transmission through coughing, sneezing, hand shaking, kissing and ear/nose piercing. Among the respondents, 52.2% correctly answered that screening of blood before transmission can prevent HIV and only 38.2% respondents knew that HIV is preventable disease. Conclusion: Women demonstrated lack of knowledge regarding HIV/AIDS and there are considerable misconceptions and myths in certain aspects which need to be clarified through educating women. Keywords: AIDS, HIV infection, women, prevention